Conflict Theory According to Johan Galtung - Fajar Khaswara; R. Yuli Ahmad Hambali (UIN Sunan Gunung Djati Bandung, 2021)
Johan Galtung is a pioneer of peace studies in the academic world, his works are still often used in peace studies and conflict resolution. His research into violence and conflict has greatly contributed to maintaining human peace. In this article, the researcher focuses on the discussion of conflict theory according to Johan Galtung. The research method in this article uses qualitative research methods with literature studies. The discussion of this research consists of: 1) Conflict according to Galtung; 2) Peace studies to resolve conflicts; 3) Benefits of peace studies in conflict resolution. This study concludes that Galtung's thoughts as a peace activist were influenced by the thoughts of other activist figures such as Mahatma Gandhi. Galtung understands that violence is not something that is easy to understand narrowly, because violence is a very broad thing and cannot be viewed from one side only.